2004
DOI: 10.1080/0963928042000306837
|View full text |Cite
|
Sign up to set email alerts
|

Changing the learning environment to promote deep learning approaches in first-year accounting students

Abstract: Developing deep approaches to learning is claimed to enhance students' engagement with their subject material and result in improved analytical and conceptual thinking skills. Numerous calls have been made for accounting educators to adopt strategies that produce such results. This paper reports on changes to the learning environment centring on the introduction of group learning activities that were designed to improve the quality of students' learning outcomes. The impact of changes in the learning environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
168
2
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(196 citation statements)
references
References 26 publications
12
168
2
9
Order By: Relevance
“…On the other hand, positive results were found when some combination of study behaviors such as attendance, homework turned in, and use of study guide, prior preparation for the class, participating in class, and coming to class on time were used (Gracia, 2003;Shaftel, 2005;Wooten, 1998 ). Group learning activities can result to an increase in students' deep learning approach, which has been known to improve analytical thinking (Hall, 2004 ). Williams and Worth (2002) conclude that attendance and note-taking predict performance.…”
Section: Importance Of Study Habits Constructsmentioning
confidence: 99%
“…On the other hand, positive results were found when some combination of study behaviors such as attendance, homework turned in, and use of study guide, prior preparation for the class, participating in class, and coming to class on time were used (Gracia, 2003;Shaftel, 2005;Wooten, 1998 ). Group learning activities can result to an increase in students' deep learning approach, which has been known to improve analytical thinking (Hall, 2004 ). Williams and Worth (2002) conclude that attendance and note-taking predict performance.…”
Section: Importance Of Study Habits Constructsmentioning
confidence: 99%
“…However, other interventions focusing on learning activities and assessment methods promoting understanding rather than reproduction have showed promising results in terms of increased use of deep learning approach and improved course grades (English et al 2004;Hall et al 2004). Instructional strategies for enhancing motivation includes focusing on the meaningful aspects of learning activities and supporting the development of appropriate learning strategy repertoires (e.g.…”
Section: Implications and Further Researchmentioning
confidence: 99%
“…However, very few studies have investigated the impact of engagement on accounting students' performance. Hall et al ͑2004͒ found that changes in the course environment can lead to changes in the learning approaches taken by students. Carnaghan and Webb ͑2007͒ found that by using group response systems ͑classroom clickers͒, students felt more engaged and actively participated more in class.…”
Section: Introductionmentioning
confidence: 99%